PENERAPAN SAK-EMKM PADA UMKM SCALE UP TANGERANG SELATAN MELALUI APLIKASI PENCATATAN INFORMASI KEUANGAN MIKRO DAN KECIL (SI APIK) - Tri Utami; Wiwit Irawati; Zulfa Rosharlianti; Dea Annisa; Dila Angraini (Abdimisi, 2019)
Financial Accounting Standards - Small, Micro and Medium Entity (SAK-EMKM) must be applied in the accounting records of UMKM actors. In the Exposure Draft  SAK -EMKM the financial statements are made very simple, the entity's financial statements are prepared using the accrual basis and business going concern assumptions, as used by entities other than micro, small and medium entities, and using the concept of a business entity. This community service (PKM) is in collaboration with the Community Empowerment House (RPM) Institute of South Tangerang. Organizing PKM activities with the aim of introducing SAK-EMKM and applying SAK-EMKM to the financial reports of UKM players in an easy way by using the SI APIK application. The target audience for this PKM is UKM players in the South Tangerang region, who are members of the Association of Community Empowerment Houses. The methods used in this PKM are counseling or lectures, tutorials, discussions, mentoring and assessments. The result of this PKM activity is that out of 100 UKM participants, only 50 UKM participants who are precise and disciplined in doing bookkeeping using SI APIK, for a period of 3 months. It is hoped that this PKM can be useful for various parties including SMEs themselves, Bank Indonesia, the Indonesian Accountants Association, the Government and academics.Keywords: SAK-EMKM, SI APIK, UMKM, RPM Institute.